Psycho-Socioeconomic bio-behavioral influences on health-related quality of life - Meghan K. Edwards; Paul D. Loprinzi (Tabriz University of Medical Sciences, 2017)
Background: The cumulative effects of psychological, socioeconomic, biological and behavioral parameters on health-related quality of life (HRQOL) has not been thoroughly evaluated, which was this study's purpose. Methods: Data from the 2005-2006 National Health and Nutrition Examination Survey were used (N = 2524 adults 20-85 years). HRQOL assessed from the Centers for Disease Control and Prevention HRQOL survey, with a higher score indicating worse HRQOL. Evaluated parameters included psychological function, socioeconomic risk, biological function and behavioral parameters. Ultimately, 14 psycho-socioeconomic bio-behavioral(PSBB) parameters were evaluated. Results: For every 1 unit increase in the PSBB index, participants had a corresponding -0.35 lower HRQOL score (β =-0.35; 95% CI: -0.44, -0.25; P<0.001). All individual components of PSBB were inversely associated with PSBB. Conclusion: PSBB was both individually and cumulatively associated with HRQOL.